2016
DOI: 10.1186/s13148-016-0293-3
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of histone deacetylase 3 (HDAC3) epigenetic signature at the interface of proinflammation and insulin resistance in patients with type 2 diabetes

Abstract: BackgroundA role of proinflammation has been implicated in the pathogenesis of diabetes, but the up-stream regulatory signals and molecular signatures are poorly understood. While histone modifications such as changes in histone deacetylase (HDAC) are emerging as novel epigenetic biomarkers, there is lack of studies to demonstrate their clinical relevance in diabetes. Therefore, we investigated the extent of HDAC machinery and inflammatory signals in peripheral blood mononuclear cells (PBMCs) from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…In a recent study, peripheral blood mononuclear cells were used to measure histone deacetylases (HDACs) activity and expression in relation to glycemia, inflammation and insulin resistance in patients with type 2 DM. Low-grade chronic inflammation and insulin resistance induced HDAC3 activity and expression, and correlated positively with circulating levels of TNF-α, IL-6, and other proinflammatory markers, and negatively with Sirt1 expression ( 114 ).…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…In a recent study, peripheral blood mononuclear cells were used to measure histone deacetylases (HDACs) activity and expression in relation to glycemia, inflammation and insulin resistance in patients with type 2 DM. Low-grade chronic inflammation and insulin resistance induced HDAC3 activity and expression, and correlated positively with circulating levels of TNF-α, IL-6, and other proinflammatory markers, and negatively with Sirt1 expression ( 114 ).…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…More specifically related to T2D, a recent study using peripheral blood mononuclear cells showed that HDAC3 activity and HDAC3 mRNA levels were positively correlated with IR [ 66 ]. Although the direct effect of other diabetes medications on the epigenome is not known, a recent intriguing publication by Zhong et al revealed that the biguanide T2D drug metformin might affect DNA methylation.…”
Section: Epigenetics Microbiota and T2dmmentioning
confidence: 99%
“…Augmentation of HDAC3 leads to diabetes, and the present study showed its association with DFU [ 42 ]. Park et al reported that knockdown of HDAC3 induces angiogenic VEGF and plasminogen activator inhibitor-1 [ 43 ].…”
Section: Discussionmentioning
confidence: 77%